2018
DOI: 10.5007/1980-0037.2018v20n5p391
|View full text |Cite
|
Sign up to set email alerts
|

Acute responses of high-intensity circuit training in women: Low physical fitness levels show higher muscle damage

Abstract: High-intensity intermittent exercise (HIIE) elicits large improvements in health and cardiorespiratory fitness (CRF). HIIE can be applied with calisthenics exercises to improve strength and endurance. The acute effects of high-intensity circuit training (HICT) considering different CRF on myological variables are unknown. The aim was measure acute effects of HICT in young women considering different levels of CRF. Twelve women were allocated in two groups, who achieve 41mLO 2 •kg -1 •min -1 or more= High Physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that HIIT protocols with good stimuli-recovery relationships may contribute to positive affective responses in healthy and unhealthy individuals 23 . Therefore, different home-based HIIT protocols may be a strategy to keep young female athletes active with physically efficient and enjoyable training 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HIIT protocols with good stimuli-recovery relationships may contribute to positive affective responses in healthy and unhealthy individuals 23 . Therefore, different home-based HIIT protocols may be a strategy to keep young female athletes active with physically efficient and enjoyable training 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 13 cases of kick injuries, 86.42% occurred in low tide period, 15.38% in critical period and 7.69% in high tide period. 8 (Table 3)…”
Section: Methodsmentioning
confidence: 99%
“…Myoglobin is an oxygen storage and transport protein found in muscle tissue [37,38]. Myoglobin is a cytoplasmic protein that is only found in the blood after skeletal or cardiac muscle injury [39]. For this reason, myoglobin is widely used as a biomarker for the diagnosis of CVD [40].…”
Section: Biosensors For the Detection Of Cardiovascular Diseasementioning
confidence: 99%